Maori rights: legal or political? - Charters, Claire (Public law review (North Ryde, N.S.W.), 2015)
Willingness of New Zealand courts to enforce legal rights where a political mechanism to address Maori rights exists - land rights - human rights - political rights - principles of the Treaty of Waitangi - takanga.
Keywords: crown law; human rights; land rights

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism